2016
DOI: 10.5430/crcp.v4n1p56
|View full text |Cite
|
Sign up to set email alerts
|

Transient Adenocorticotropic Hormone deficiency in an infant

Abstract: Background: Isolated Adenocorticotropin Hormone (ACTH) deficiency is a rare disorder, characterized by secondary adrenal insufficiency with a low or absent cortisol production, normal secretion of other pituitary hormones and absence of structural pituitary defects. Case summary: The patient was the product of a 28 weeks gestation, clomiphen induced to a 40-year-old, gestational diabetic mother. He was ventilated for 30 days, and was diagnosed to have grade IV Retina of Prematurity (ROP). He suffered from recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Various types of neurohypophyseal abnormalities have been identified in MRI scans of patients with isolated GHD. Similar to our findings, the most common type of abnormality reported in the literature in patients with isolated GHD is pituitary hypoplasia, which is characterized by a small or underdeveloped pituitary gland [17]. In a study reported by Chen et al, pituitary hypoplasia was the most frequent MRI abnormality in their study on pediatric patients with GHD [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Various types of neurohypophyseal abnormalities have been identified in MRI scans of patients with isolated GHD. Similar to our findings, the most common type of abnormality reported in the literature in patients with isolated GHD is pituitary hypoplasia, which is characterized by a small or underdeveloped pituitary gland [17]. In a study reported by Chen et al, pituitary hypoplasia was the most frequent MRI abnormality in their study on pediatric patients with GHD [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…[2][3][4][5][6][7][8][9][10][14][15][16] Insulin Tolerance Test (ITT) is considered the gold standard test to evaluate the hypothalamic pituitary adrenal (HPA), but has its disadvantages in clinical practice and that is the reason we prefer to the synacthen test, in most cases. 17 The patients presented here 18,19 were diagnosed as having isolated Adrenocorticotrophic Hormone (ACTH) deficiency according to the typical endocrinological findings as well as hormonal revaluation after a sufficient time interval on replacement therapy. The possible path physiologic mechanisms leading to this is poorly understood.…”
Section: Discussionmentioning
confidence: 99%